Becoming Precarious? Precarious Work and Life Trajectories After Retrenchment. (July 2020) - Barnes, Tom; Weller, Sally A.
Much of the large literature on precarious work has largely tended to assume that precarity is shaped by job quality: that precarious work leads to precarious lives. This paper adds to the literature by questioning this line of causality and highlighting the broader range of influences shaping the lives of older workers who enter precarious work after retrenchment from secure, long-term careers. Drawing on a study of Australia's automotive manufacturing industry, which closed in 2017, this article finds that for older retrenched workers, exposure to precarious employment sharpened life precarity for some but did not lead to precarious lives for others. Instead of a uniform transition from security to precarity, these workers' life trajectories diverged depending on their household-scale financial security. Key issues influencing the likelihood of older workers' lives becoming precarious were enterprise benefits and asset wealth accumulated through their previous careers.